Acute Cannabinoids Produce Robust Anxiety-Like and Locomotor Effects in Mice, but Long-Term Consequences Are Age- and Sex-Dependent - Kasten, Chelsea R.; Zhang, Yanping; Boehm, Stephen L. (Frontiers in Behavioral Neuroscience, 2019)
The rise in cannabinoid legalization and decriminalization in the US has been paired with an increase in adolescents that perceive marijuana as a “no risk” drug. However, a comprehensive review of human literature indicates that cannabinoid usage may have both beneficial and detrimental effects, with adolescent exposure being a critical window for harming cognitive development. Although the cannabinoids Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD) are often used together for recreational and medical purposes, no study has previously observed the acute and long-lasting effects of THC+CBD in a battery of behavioral assays analogous to subjective human reports. The current study observed the acute and long-term effects of THC, CBD, and THC+CBD on object memory, anxiety-like behavior, and activity levels in adolescent and adult mice of both sexes. Acute THC alone and in combination with CBD resulted in robust effects on anxiety-like and locomotor behavior. A history of repeated cannabinoid treatment followed by a period without drug administration resulted in minimal effects in these behavioral assays. Most notably, the strongest effects of repeated cannabinoid treatment were seen in adult females administered THC+CBD, which significantly impaired their object recognition. No effects of repeated cannabinoid history were present on hippocampal protein expression. These studies represent a detailed examination of age- and sex-effects of acute and repeated cannabinoid administration. However, the acute and long-term effects of THC with and without CBD on additional behaviors in adolescents and adults will need to be examined for a more complete picture of these drug effects.